2021
DOI: 10.1371/journal.pone.0245547
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological findings of adult hospitalized patients with community-acquired pneumonia from SARS-CoV-2 and endemic human coronaviruses

Abstract: Endemic human coronaviruses (HCoVs) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are members of the family Coronaviridae. Comparing the findings of the infections caused by these viruses would help reveal the novel characteristics of SARS-CoV-2 and provide insight into the unique pathogenesis of SARS-CoV-2 infection. This study aimed to compare the clinical and radiological characteristics of SARS-CoV-2 and endemic HCoVs infection in adult hospitalized patients with community-acquired pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…3b). We preferred a four-class taxonomy, as further distinguishing COVID-19 from community-acquired pneumonia 24,25 can help deliver more commendatory clinical treatments where the bacterial and the viral are two primary pathogens of community-acquired pneumonia 26 (Fig. 2c); however, given that different institutions are accompanied by various annotating protocols, it is more feasible for the model to learn to discriminate COVID-19 from all non-COVID-19 cases.…”
Section: Developing a Local Accurate Ai Diagnostic Modelmentioning
confidence: 99%
“…3b). We preferred a four-class taxonomy, as further distinguishing COVID-19 from community-acquired pneumonia 24,25 can help deliver more commendatory clinical treatments where the bacterial and the viral are two primary pathogens of community-acquired pneumonia 26 (Fig. 2c); however, given that different institutions are accompanied by various annotating protocols, it is more feasible for the model to learn to discriminate COVID-19 from all non-COVID-19 cases.…”
Section: Developing a Local Accurate Ai Diagnostic Modelmentioning
confidence: 99%
“…However, the rest of the chest CT findings were not significantly different between them [15]. On the other hand, a study revealed that the chest CT findings of SARS-CoV-2 and endemic HCoV community-acquired pneumonia (CAP) are dissimilar, especially in the groundglass opacities (GGOs) pattern, which distinguish these two CAP from each other [16]. However, this issue remains controversial yet [17].…”
Section: Tablementioning
confidence: 99%